ANALISIS NON-LINIER PENAMPANG PILAR JEMBATAN BETON BERTULANG YANG TERBEBANI DIPERKUAT DENGAN JAKET BETON - Daniel Dixon Octora (Jurnal Jalan-Jembatan, 2019)
ABSTRACT In many design practices, assumptions that are used in retrofitting concrete structural elements often ignore the condition of initial load. The concrete structural elements which are loaded by the existing load causing initial strain on the existing cross-section before retrofit is applied. This research will study this parameter in the non-linear section analysis of concrete cross-sections retrofitted by concrete jacketing. A hollow column cross-section is examined as an example, wherein the parameter of initial load considered in two conditions which are above and below the yield point of existing section. The non-linear section analysis was performed by developing a computer package program created in Matlab language code with a fiber section approach to obtain the moment-curvature relationship which is obtained by achieving a force equilibrium condition, assuming that the existing cross-section have similar stiffness due to temporary repair applied before jacketing application and a perfect bond between the concrete and the reinforcing steel. The retrofitted cross-section capacity and ductility will be carried out in conditions wherein the initial load approach is calculated compared with the monolithic approach. The object of this research is applied on Cisomang Bridge were located on Cipularang Highway, in which on 2016, the pier of this bridge was cracked because of the foundation shift caused by the accumulation of soil movement of the Cisomang river. The results showed that initial load parameters did not significantly affect cross-sectional capacity when compared with the monolithic approach (â‰¤ 7%). Key words: concrete jacketing, programming, Matlab, initial load, moment-curvature, bridge pier.